EKSPLORASI AKTIVITAS SISWA MELALUI MODEL INTERAKSI LEIKIN DALAM PEMBELAJARAN MATEMATIKA - Sofia Sa'o; Finsensius Yesekiel Naja; Agustina Mei (Program Studi Pendidikan Matematika, 2020)
This research focused on the difficulty of students doing interaction activities in learning mathematics in school. Sometimes even smart students will get used to silence in class. Students are not accustomed to actively interacting, even though student activities are very important in the process of learning mathematics. Activities that occur in learning, include several aspects such as listening to the teacher's explanation, asking if there is something that has not been understood, answering the question of the teacher or other friends, having active discussions if allowed group work, solving practice questions if they are given by the teacher and so on. The activities included in it are interactive activities. Interaction in this research is an activity that occurs about the needs of the learning process, namely the relationship between teacher and student, student and teacher, student and student, and student and learning resources. The method used in this research is how the interaction that occurs is related to the interaction model. The expected results of this study are students can actively interact in every learning process in school.